Commercial Policy under Ulèëbalangs: A Factor Contributing to Cumbôk War - Syukri Rizki; Ikhwan Rahmatika Latif (IKAT: The Indonesian Journal of Southeast Asian Studies, 2020)
Adat chiefs in Aceh – locally termed as ulèëbalang – served as one of the three most compelling socio-political forces besides the sultan and ulamas. As regional rulers in the Aceh Kingdom, they were appointed as leaders through the approval of the Sultan of Aceh. The ulèëbalangs would possess leadership with the reinforcement of a Sarakata letter affixed with a “Cap Sikureueng” (Kingdom of Aceh’s Seal). Not only did ulèëbalangs serve as the ruler in terms of Executive administration, but also controlled almost all life sectors of the Acehnese people like trade, court, agriculture and plantation, which the Sultan hardly ever touched. With this legitimate power, the ulèëbalangs were rightful to issue commercial policies in their regional territories. In exercising their power, they often acted recklessly towards their subjects. The objective of this study was to identify whether the commercial policy imposed by the ulèëbalangs was one of the factors contributing to the happening of the Cumbôk war in 1945. This study mainly focused on ulèëbalangs who ruled in the Pidie area by studying secondary data available online and offline. The findings of this study confirmed that it was evident that the ulèëbalangs’ malfeasance in controlling commerce, among other things, did contribute to the tension arising between ulamas and ulèëbalangs, which eventually broke out as the Cumbôk war.